Effect of sodium hypochlorite on the bond strength of an adhesive system to superficial and deep dentin Efeito do hipoclorito de sódio na resistência de união de um sistema adesivo na dentina superficial e profunda - Ninoshka Uceda-Gómez; Alessandra Reis; Marcela Rocha de Oliveira Carrilho; Alessandro Dourado Loguercio; Leonardo Eloy Rodriguez Filho (University of São Paulo, 2003)
The objective of this study was to evaluate the bond strength to superficial (SU) and deep (D) dentin, accessed via apical (DA) or occlusal (DO), using One-Step adhesive system applied according to the manufacturer's instructions (C) or following deproteinization with 10% sodium hypochlorite (H) for 60s, after acid etching. Three sound extracted human molars were prepared for each experimental condition. Restorations were performed using Z100 in 2mm increments, each one being light-cured for 40s. Teeth were longitudinally sectioned to obtain stick-shaped specimens with a cross-sectional area of 0.8mm², which were submitted to bond strength test (0.6mm/min). Results obtained after statistical analysis using a two-way ANOVA (substrate vs. surface treatment) and Tukey's test were: SU (35.4 ± 12.3), DO (26.5 ± 8.5), DA (26.1 ± 10.2) following conventional surface treatment, and SU (28.82 ± 12.7), DO (24.3 ± 8.3) and DA (23.5 ± 8.5), after surface treatment using sodium hypochlorite. The interaction of the factors was not significant (p>0.05). However, the main factors were significant (p<0.05). Mean bond strength values in superficial dentin were statistically superior to deep dentin (p<0.05), although no statistically significant difference was observed between the two via of access to deep dentin (SU>DO=DA). The conventional surface treatment resulted in higher bond strength values than the sodium hypochlorite treatment (p<0.05). It was concluded: 1) bond strength values were higher in superficial dentin, 2) no difference was found between the two deep substrate preparations, and 3) the application of sodium hypochlorite following dentin acid etching may reduce bond strengths. O objetivo foi avaliar a resistência de união (RU) de dentina superficial (SU) e profunda (P), obtida por acesso apical (PA) ou oclusal (PO), ao adesivo One-Step com (H) ou sem aplicação de hipoclorito de sódio a 10% (C) após o condicionamento ácido. Para os 6 grupos foram utilizados seis molares hígidos. Nos grupos SUC, PAC e POC, o adesivo e a resina Z100 foram aplicados. Nos grupos SUH, PAH e POH, após condicionamento, aplicou-se H por 60s, adesivo e Z100. Os dentes foram fatiados em cortes paralelos e perpendiculares para a obtenção de cp de 0,8mm² e testados sob tração (0,6mm/min). Os valores de RU foram submetidos a ANOVA de dois fatores. Não se detectou diferença para a interação (p=0,209), porém os fatores principais foram diferentes (p<0.05). Os resultados do tratamento C para os diferentes substratos foram: SU (35,4 ± 12,3), PO (26,5 ± 8,5), PA (26,1 ± 10,2) e para o tratamento H foram: SU (28,82 ± 12,7), PO (24,3 ± 8,3) e PA (23,5 ± 8,5). Os valores de RU em dentina SU foram estatisticamente superiores do que na dentina profunda (p<0,05), não foi observado diferença estatística nas duas vias de acesso para dentina profunda (SU>PO=PA). Os valores de RU com o tratamento C foram superiores aos obtidos quando utilizou-se o H. Conclui-se que: 1) os valores de RU foram maiores em dentina SU; 2) não houve diferença entre os dois substratos de dentina profunda; 3) aplicação do hipoclorito de sódio após o condicionamento diminuiu a RU.